Redox-active organic-inorganic hybrid polyoxometalate micelles - Kastner, Katharina; Kibler, Alexander J.; Karjalainen, Erno; Fernandes, Jesum A.; Sans, Victor; Newton, Graham (Royal Society of Chemistry, 2017)
A redox-active hybrid organic-inorganic polyoxometalate surfactant showed solvent-dependent self-assembly to form nano-scale architectures. The supramolecular assemblies exhibited contrasting electronic structure and redox activity to their molecular building units, and were found to be stable under electrochemical reduction and re-oxidation.